2005
DOI: 10.14411/eje.2005.088
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of HP1 and methylated H3 histones as heterochromatic epigenetic markers in the holocentric chromosomes of the cabbage moth, Mamestra brassicae (Lepidoptera)

Abstract: Abstract. The methylated H3 histone and heterochromatin protein 1 (HP1) are markers of heterochromatin in several eukaryotes possessing monocentric chromosomes. In order to confirm that these epigenetic markers of heterochromatin are evolutionary conserved, the distribution of methylated H3 histones and HP1 homologues on the holocentric chromosomes of the cabbage moth Mamestra brassicae (Lepidoptera) were studied. In particular, PCR experiments with degenerated primers identified a HP1 homologue (called MbHP1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
4
4
0
Order By: Relevance
“…In the lane containing the protein extract from SL2 Drosophila cells, the HP1 antibody, as expected, recognized an antigen with an apparent molecular weight of 34 kDa (Eissenberg & Elgin 2000) ( Figure 3, left). In the lane containing the whole-protein extract from M. brassicae cells, a single band of about 20 kDa was observed, as expected on the basis of the data reported by Borsatti & Mandrioli (2005) (Figure 3, centre). In the lane containing the protein extract from aphid tissues, the antibody recognized a single protein with an approximate weight of 28 kDa that is coherent with the estimated weight of the predicted ApHP1 peptide (Figure 3, right).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In the lane containing the protein extract from SL2 Drosophila cells, the HP1 antibody, as expected, recognized an antigen with an apparent molecular weight of 34 kDa (Eissenberg & Elgin 2000) ( Figure 3, left). In the lane containing the whole-protein extract from M. brassicae cells, a single band of about 20 kDa was observed, as expected on the basis of the data reported by Borsatti & Mandrioli (2005) (Figure 3, centre). In the lane containing the protein extract from aphid tissues, the antibody recognized a single protein with an approximate weight of 28 kDa that is coherent with the estimated weight of the predicted ApHP1 peptide (Figure 3, right).…”
Section: Resultssupporting
confidence: 86%
“…In view of this, immunodetection of HP1 and Me9H3 was performed, indicating that aphid constitutive heterochromatin is enriched both in H3 histone monomethylated at lysine 9 and in HP1 proteins. These epigenetic markers are, therefore, true heterochromatic markers not only for vertebrate chromosomes but also for insect heterochromatin, as previously reported in the dipteran D. melanogaster (Cowell et al 2002), in the homopteran P. citri (Cowell et al 2002) and in the lepidopteran M. brassicae (Borsatti & Mandrioli 2005).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, H3 histone monomethylated at lysine 9 and HP1 are common epigenetic markers for heterochromatin, both in vertebrates and invertebrates (e.g. Jacobs et al, 2001;Lachner et al, 2001;Cowell et al, 2002;Borsatti & Mandrioli, 2005). Both in A. pisum (Mandrioli & Borsatti, 2007) and A. nerii (Mandrioli et al, 2011), the only aphid species to date studied at the epigenetic level, Me9H3 and HP1 have been localized in C-positive areas indicating that aphid C-heterochromatin is enriched in both of these epigenetic markers.…”
Section: Epigenetic Markers Of Aphid Heterochromatinmentioning
confidence: 99%
“…More importantly H3K9me2 signal surrounding centromeres is thought to be lost in these organisms, unlike holocentric C.elegans (Steiner et Henikoff 2014). Previous studies conducted on Lepidopteran showed nonetheless that H3K9me2 is still associated to repeated DNA at rDNA loci and sexual chromosomes (Stanojcic et al 2011; Borsatti et Mandrioli 2013).…”
Section: Introductionmentioning
confidence: 95%